Association between neutrophil percentage-to-albumin ratio and contrast-associated acute kidney injury in patients without chronic kidney disease undergoing percutaneous coronary intervention. Issue 2 (February 2022) - He, Hao-Ming; Zhang, Si-Cheng; He, Chen; You, Zhe-Bin; Luo, Man-Qing; Lin, Mao-Qing; Lin, Xue-Qin; Zhang, Li-Wei; Lin, Kai-Yang; Guo, Yan-Song
Highlights: We assessed neutrophil percentage-to-albumin ratio (NPAR) on admission in patients without chronic kidney disease (CKD) undergoing percutaneous coronary intervention (PCI). High NPAR (>15.7) was associated with contrast-associated acute kidney injury. High NPAR (>15.7) was an independent predictor of long-term mortality. NPAR may assist risk stratification in patients without CKD undergoing PCI. Abstract: Background: Neutrophil and albumin are well-known biomarkers of inflammation, which are highly related to contrast-associated acute kidney injury (CA-AKI). We aim to explore the predictive value of neutrophil percentage-to-albumin ratio (NPAR) for CA-AKI and long-term mortality in patients without chronic kidney disease (CKD) undergoing elective percutaneous coronary intervention (PCI). Methods: We retrospectively observed 5083 consenting patients from January 2012 to December 2018. CA-AKI was defined as an increase in serum creatinine ≥50% or 0.3 mg/dL within 48 h after contrast medium exposure. Results: The incidence of CA-AKI was 5.6% (n=286). The optimal cut-off value of NPAR for predicting CA-AKI was 15.7 with 66.8% sensitivity and 61.9% specificity [C statistic=0.679; 95% confidence interval (CI), 0.666-0.691]. NPAR displayed higher area under the curve values in comparison to neutrophil percentage ( p < 0.001) and neutrophil-to-albumin ratio (NAR) ( p < 0.001), but not albumin ( p = 0.063). However, NPAR significantly improved the prediction of CA-AKI assessed by the continuous net reclassification improvement (NRI) and integrated discrimination improvement (IDI) compared to neutrophil percentage (NRI=0.353, 95% CI: 0.234-0.472, p < 0.001; IDI=0.017, 95% CI: 0.010-0.024, p < 0.001) and albumin (NRI=0.141, 95% CI: 0.022-0.260, p = 0.020; IDI=0.009, 95% CI: 0.003-0.015, p = 0.003) alone. After adjusting for potential confounding factors, multivariate analysis showed that NPAR >15.7 was a strong independent predictor of CA-AKI (odds ratio =1.90, 95% CI: 1.38-2.63, p < 0.001). Additionally, NPAR >15.7 was significantly associated with long-term mortality during a median of 2.9 years of follow-up (hazard ratio =1.68, 95% CI: 1.32-2.13; p < 0.001). Conclusions: NPAR was an independent predictor of CA-AKI and long-term mortality in patients without CKD undergoing elective PCI. Graphical abstract: Image, graphical abstract